Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1177/10436596221125900
|View full text |Cite
|
Sign up to set email alerts
|

Donor Breast Milk Banking: Knowledge and Attitudes of Iranian Mothers

Abstract: Introduction: Milk donation is allowed in Islam and considered a virtue, though according to Islam Sharia, feeding donated milk of other mothers leads to kinship between infants, complicating milk donation programs in Islamic countries. This study aimed to determine the knowledge and attitude of Iranian Muslim mothers regarding milk donation and milk banks. Methods: In this cross-sectional descriptive-analytic study, 634 mothers of infants below 1 year of age were recruited using cluster random sampling from h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…A well-designed educational program is crucial to improving breastfeeding mothers' knowledge and behavior regarding milk donation. Especially in Iran, some Muslim mothers may potentially avoid using DHM or donating their breastmilk because they may wrongly assume that milk donation can lead to milk kindship between infants or is not allowed in Islam even though milk donation is perfectly allowed and praised as a virtue in Islam, so they need to be informed about Islam Sharia related to milk donation (34). In addition, Iranian mothers have a positive attitude towards breastfeeding and the prevalence of exclusive breastfeeding among them is at a satisfactory level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A well-designed educational program is crucial to improving breastfeeding mothers' knowledge and behavior regarding milk donation. Especially in Iran, some Muslim mothers may potentially avoid using DHM or donating their breastmilk because they may wrongly assume that milk donation can lead to milk kindship between infants or is not allowed in Islam even though milk donation is perfectly allowed and praised as a virtue in Islam, so they need to be informed about Islam Sharia related to milk donation (34). In addition, Iranian mothers have a positive attitude towards breastfeeding and the prevalence of exclusive breastfeeding among them is at a satisfactory level.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is expected that there will be an increase in the number of infants who are admitted to NICUs and, Increasing the number of milk banks and improving the behavior of milk donation are crucial in ensuring the survival and well-being of these infants. Reviewing the literature on the knowledge, attitude, and behavior of mothers regarding milk donation and milk banks has revealed that mothers often do not have enough knowledge about milk donation and HMBs, and especially in Iran, despite the favorable knowledge and positive attitude of women toward breastfeeding, the availability of information and education about milk bank to mothers is very limited and these data speak to the need for designing some educational interventions provided by health professionals in order to boost mothers' knowledge and promote factors that are important in behavior of breastmilk donation in order to encourage potential donor to donate their breast milk to HMBs (11,25,27,(32)(33)(34)(35) meanwhile, in regard to breastfeeding and milk donation, it seems that behavioral theory-based educational interventions have the ability to provide a useful framework to give essential information to mothers and improve their understanding on this subject (25,36). Thus, this quasi-experimental study seeks to assess whether the educational program based on theory of planned behavior (TPB) in uences breastfeeding mothers' decision to donate their breast milk.…”
Section: Introductionmentioning
confidence: 99%
“…In Muslim countries, the development of HMB facilities has remained constrained in number and scale. 14,[16][17][18][19][20][24][25][26][27][28][29][30][31][32][33][34][35][36] The Islamic tradition recognizes breast milk as the optimal source of nutrition for infants, but religious-ethical reservations have curtailed the enthusiasm to develop HMBs. 37 There are a few notable, pioneering HMBs in Turkey, Kuwait, Iraq, Iran, Pakistan, and Malaysia.…”
Section: Human Milk Bank Movement I N T H E Islamic Worldmentioning
confidence: 99%
“…37 There are a few notable, pioneering HMBs in Turkey, Kuwait, Iraq, Iran, Pakistan, and Malaysia. 24,25,33,35,38 Kuwait, Iran, and Malaysia have a few more facilities in planning. 25 There is a need for religious education so that the involved parties truly understand the message from the leaders.…”
Section: Human Milk Bank Movement I N T H E Islamic Worldmentioning
confidence: 99%
“…Reviewing the literature on milk donation behavior has revealed that mothers often do not have enough knowledge about milk donation and HMBs, and especially in Iran, despite the favorable knowledge and positive attitudes of women toward breastfeeding, the availability of information and education about milk bank to mothers is very limited. Therefore, there is a need for educational interventions by health professionals to increase mothers’ knowledge and promote factors that influence milk donation behavior, and to encourage potential donors to donate their breast milk to HMBs [ 10 12 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%